The Differences of Taxpayer Compliance Before and After Tax Amnesty Stimulus - Subadriyah Subadriyah; Siti Aliyah (University of Islam Malang, 2018)
Tax amnesty is a type of remission program for taxpayers where they are freed from their tax obligations but, in exchange for the tax liability forgiveness, have to pay a redemption amount of money and disclose incomplete or unreported income in their previous tax periods, without having to face theadministrative penalty or tax prosecution. The short-term purpose of tax amnesty is to increase the country's income in large quantities in a short time. In the long-term, this program is intended to form a wider database so that the government can increase the number of taxpayers and level of tax compliance. This study aims to determine the differences in taxpayer compliance during the periods before (pre-test) and after (pro-test) the Indonesian Tax Amnesty program which ended on March 31, 2017. The population was taken from the total data of taxpayers registered in KPP Pratama Jepara. The sample for this research includes 100 respondents based on Slovin's formula calculation. The sampling was done using purposive sampling, and the type of data used was primary data collected via questionnaire distribution. The method used for the data analysis was a paired sample t-test. The results showed that the taxpayer compliance between the pretest and protest of tax amnesty program changed. This difference indicates an increase in taxpayer compliance, although still very low.